2006
DOI: 10.1007/s00705-006-0847-3
|View full text |Cite
|
Sign up to set email alerts
|

Infection of soybean by cucumber mosaic virus as determined by viral movement protein

Abstract: To characterize the host range determinant of the soybean strain of Cucumber mosaic virus (CMV) we analyzed a series of pseudorecombinants and chimeric viruses between infectious transcripts from two soybean strains (CMV-SC and CMV-SD) and an ordinary strain (CMV-Y). CMV-Y could not infect soybeans, even locally. Systemic infection of the two soybean-adapted soybean isolates on soybean plants mapped to RNA3. Chimeric RNA3s from between CMV-SC and CMV-Y, and chimeric RNA3s from between CMV-SC and CMV-SD, were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…For viral infection, a pseudorecombinant virus that consists of RNA components derived from different CMV strains was made because CMV‐Y, the origin of all three RNA components of our original vector system, did not infect soybean. Previous analysis demonstrated that a pseudorecombinant virus containing RNA3 derived from the soybean strain of CMV (CMV‐Sj) could infect soybeans (Senda et al ., 2004; Hong et al ., 2007; Matsuo et al ., 2007). Accordingly, CMV‐Y RNA1 (Y1) and CMV‐Sj RNA3 (S3) were mixed with A1:CHS7, to create a pseudorecombinant virus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For viral infection, a pseudorecombinant virus that consists of RNA components derived from different CMV strains was made because CMV‐Y, the origin of all three RNA components of our original vector system, did not infect soybean. Previous analysis demonstrated that a pseudorecombinant virus containing RNA3 derived from the soybean strain of CMV (CMV‐Sj) could infect soybeans (Senda et al ., 2004; Hong et al ., 2007; Matsuo et al ., 2007). Accordingly, CMV‐Y RNA1 (Y1) and CMV‐Sj RNA3 (S3) were mixed with A1:CHS7, to create a pseudorecombinant virus.…”
Section: Resultsmentioning
confidence: 99%
“…Different strains of CMV preferentially infect different plant species. For example, the soybean strain of CMV can infect soybean (Senda et al ., 2004; Hong et al ., 2007; Matsuo et al ., 2007; present study), while ordinary strains, such as CMV‐Y, CMV‐L, or CMV‐O, can infect various plant species, e.g. Petunia hybrida (Koseki et al ., 2005) and A .…”
Section: Discussionmentioning
confidence: 99%
“…The difference of host range and/or infectivity between the CMV-209 and other reported CMV strains in tested host plants observed in this study might be due to sequence changes in CMV-209 RNA genome segments. In this regard, it is worth mentioning that the RNA3 segment including 3a and CP proteins has been reported as a host range determinant and thus might be more responsible as host-interactive constraints than the other viral gene products (Hong et al, 2007; Hong et al, 2003; Roossinck, 2002; Ryu et al, 1998). We are currently conducting experiments with reasserted RNA segment using several CMV strains including Fny and 209 to further determine whether RNA3 segment is responsible for determining host range and/or infectivity.…”
Section: Resultsmentioning
confidence: 99%
“…CMV seed transmission in susceptible bean cultivars is up to 49 % [7] and is retained in the seed for about 27 months during storage [3]. CMV strains earlier described mainly based on host range, symptoms, vectors, serological properties and nucleic acid sequence [26] are currently divided into two major groups (subgroup 1 and subgroup 2) based on serological and sequence similarities [18].…”
Section: Introductionmentioning
confidence: 99%